The master chief : part one [videorecording (DVD)] / written and directed by Chris Soriano. - Soriano, Chris; Soriano, Chris; Soriano, Hillary; Soriano, Hillary; Mitchell, Warren; Torres, Rhandy; Tolentino. Georgiana (Gravitas Ventures LLC., 2023)
A young Filipino sailor is confronted with the stark reality of racial tension aboard a Naval ship.